ΜHall Chip for Sensitive Detection of Bacteria. Issue 9 (12th March 2013) - Issadore, David; Chung, Hyun Jung; Chung, Jaehoon; Budin, Ghyslain; Weissleder, Ralph; Lee, Hakho
Abstract Sensitive, rapid and phenotype‐specific enumeration of pathogens is essential for the diagnosis of infectious disease, monitoring of food chains, and for defense against bioterrorism. Microbiological culture and genotyping, techniques that sensitively and selectively detect bacteria in laboratory settings, have limited application in clinical environments due to high cost, slow response times, and the need for specially trained staff and laboratory infrastructure. To address these challenges, we developed a microfluidic chip‐based micro‐Hall (μHall) platform capable of measuring single, magnetically tagged bacteria directly in clinical specimens with minimal sample processing. We demonstrated the clinical utility of the μHall chip by enumerating Gram‐positive bacteria. The overall detection limit of the system was similar to that of culture tests (∼10 bacteria), but the assay time was 50‐times faster. This low‐cost, single‐cell analytical technique is especially well‐suited to diagnose infectious diseases in resource‐limited clinical settings.